A Systematic Review and Meta-Analysis of Epidemiology of Risky Sexual Behaviors in College and University Students in Ethiopia, 2018. (20th March 2019) - Amare, Tadele; Yeneabat, Tebikew; Amare, Yohannes
Abstract : Background . Risk of sexual ill-health occurs with the onset of unsafe sexual activity, mostly among the adolescents, and continues as long as the risky activities are engaged in. Globally, and in Africa, adolescent AIDS-related mortality among adolescents has been increasing. Therefore, a systematic review and meta-analysis of epidemiology of risky sexual behaviors in college and university students in Ethiopia is mandatory. Methods . We conducted extensive search of articles as indicated in the guideline of reporting systematic review and meta-analysis (PRISMA). Databases such as PubMed, Global Health, Africa-wides, Google advance search, Scopus, and EMBASE were accessed for literature search. The pooled estimated effect of epidemiology of risky sexual behaviors and associated factors were analyzed by using the random effects model meta-analysis and 95% CI was also considered. PROSPERO registration number isCRD42018109277 . Result . A total of 18 studies with 10, 218 participants were encompassed in this meta-analysis. The estimated pooled prevalence of risky sexual behaviors among college and university students was 41.62%. Being male [OR: 2.35, with 95% (CI; 1.20, 4.59)], alcohol use [OR: 2.68, with 95% CI; (1.67, 4.33)] and watching pornography [OR: 4.74, with 95% CI; (3.21, 7.00)] were positively associated with risky sexual behaviors. Conclusion and recommendation . Risky sexual behavior among students was high. Educational institutions should give special attention for male sex, alcohol user, and students who watch pornography.